Beyond the beaten paths of forecasting call center arrivals: on the use of dynamic harmonic regression with predictor variables - Theresa Maria Rausch; Tobias Albrecht; Daniel Baier (Journal of Business Economics, 2021)
Modern call centers require precise forecasts of call and e-mail arrivals to optimize staffing decisions and to ensure high customer satisfaction through short waiting times and the availability of qualified agents. In the dynamic environment of multi-channel customer contact, organizational decision-makers often rely on robust but simplistic forecasting methods. Although forecasting literature indicates that incorporating additional information into time series predictions adds value by improving model performance, extant research in the call center domain barely considers the potential of sophisticated multivariate models. Hence, with an extended dynamic harmonic regression (DHR) approach, this study proposes a new reliable method for call center arrivals' forecasting that is able to capture the dynamics of a time series and to include contextual information in form of predictor variables. The study evaluates the predictive potential of the approach on the call and e-mail arrival series of a leading German online retailer comprising 174~weeks of data. The analysis involves time series cross-validation with an expanding rolling window over 52~weeks and comprises established time series as well as machine learning models as benchmarks. The multivariate DHR model outperforms the compared models with regard to forecast accuracy for a broad spectrum of lead times. This study further gives contextual insights into the selection and optimal implementation of marketing-relevant predictor variables such as catalog releases, mail as well as postal reminders, or billing cycles.
Keywords: C22; C53; L81; M30; 650; Forecasting; Call center arrivals; Dynamic harmonic regression; Time series analysis; Machine learning; Customer relationship management